Memory And Imagination: The Paschal Triduum Teaching How To Live And How To Die. - Eschenauer, Donna (Religious Education)
Memory and imagination, complex activities of the brain, act as the cornerstone for ritual prayer. These brain functions ground us in hope and aid in our discovery of what it means to be human at a deep level. This article explores the ritual of the Paschal Triduum, the Roman Catholic Church's highest expression of faith. It interprets the Triduum as a ritual pilgrimage of memory and hope that reveals a cycle of deep human activity and religious imagination. Drawing insight from the work of Gabriel Moran, the article maintains that the Triduum discloses a profound rhythm of life, namely, showing participants how to live and how to die.